Preferable Transplant Site for Hepatocyte Transplantation in a Rat Model. (13th September 2021) - Ogasawara, Hiroyuki; Inagaki, Akiko; Fathi, Ibrahim; Imura, Takehiro; Yamana, Hiroki; Saitoh, Yoshikatsu; Matsumura, Muneyuki; Fukuoka, Kengo; Miyagi, Shigehito; Nakamura, Yasuhiro; Ohashi, Kazuo; Unno, Michiaki; et al.
Intraportal injection is regarded as the current standard procedure of hepatocyte transplantation (HTx). In islet transplantation, which shares many aspects with HTx, recent studies have clarified that instant blood-mediated inflammatory reaction (IBMIR), characterized by strong innate immune responses, can cause poor engraftment, so other transplant sites to avoid such a reaction have been established. Although IBMIR was reported to occur in HTx, few reports have evaluated alternative transplant sites for HTx. In this study, we sought to determine the optimum transplant site for HTx. Rat hepatocytes (1.0 × 10 7 ) were transplanted at the 9 transplant sites (intraportal (IPO), intrasplenic (IS), liver parenchyma, subcutaneous, intraperitoneal, renal subcapsular, muscle, inguinal subcutaneous white adipose tissue, and omentum) of analbuminemic rats. The serum albumin levels, immunohistochemical staining (albumin, TUNEL, and BrdU), and in vivo imaging of the grafts were evaluated. The serum albumin levels of the IPO group were significantly higher than those of the other groups ( p < .0001). The BrdU-positive hepatocyte ratio of liver in the IS group (0.9% ± 0.2%) was comparable to that of the IPO group (0.9% ± 0.3%) and tended to be higher than that of the spleen in the IS group (0.5% ± 0.1%, p = .16). Considering the in vivo imaging evaluation and the influence of splenectomy, the graft function in the IS group may be almost entirely achieved by hepatocytes that have migrated to the liver. The present study clearly showed that the intraportal injection procedure is more efficient than other procedures for performing HTx